Characterization of child sexual abuse from medical records - Bravo García, Leslie (2016)
The problem of sexual abuse affects children in all contexts and especially Colombia. Registering a high rate of sexually abused children, so this research provides a categorization of this scourge. As methodology, analysis of medical records, with a validated by experts instrument, in which it was established that both sexes are prone to abuse, being slightly higher in girls than in boys, as the context in which mostly occurs was used this problem is in the family, and the main type of abuse that is physical contact externalized; similarly, it highlights the fact that most abusive events are shown in urban areas.